Food Texture Design and Optimization. - Dar, Yadunandan Lal (Institute of Food Technologists Series., 2014)
Food texture has evolved to be at the forefront of food formulation and development. Food Texture Design and Optimization presents the latest insights in food texture derived from advances in formulation science as well as sensory and instrumental measurement. This unique volume provides practical insights for professionals who are starting in the field as well as experts looking to enhance their knowledge or expand into new areas. The first part of this book presents case studies on formulating products in a broad variety of applicationsegments, such as cheese, ice-cream.